INFLUENCE OF GROWTH AND YIELD ATTRIBUTES OF WHEAT (TRITICUM AESTIVUM L.) BY ORGANIC AND INORGANIC SOURCES OF NUTRIENTS WITH RESIDUAL EFFECT UNDER DIFFERENT FERTILITY LEVELS - V. S. MEENA,; B. R. MAURYA,; R. VERMA,; R. MEENA,; R. S. MEENA,; G. K. JATAV,; D. K. SINGH, (The Bioscan, 2013)
This manuscript focuses on the effect of concentrate organic manure (wellgrow grain and wellgrow soil) and different levels of nutrients on growth and yield component of wheat under different levels of fertility. Significant improvement in terms of growth parameters like plant height, number of tillers, dry matter production and number of productive tillers with application of 100% NPK + 300 kg wellgrow grain/ha and at par with application of 100% NPK + 300 kg wellgrow soil/ha, 100% NPK + 200 kg wellgrow grain/ha. Treatment receiving 100% NPK + 300 kg wellgrow grain/ha resulted maximum effective tillers/hill (350 m-2), grain yield (41.2 q/ha). Treatment 100% NPK + 300 kg wellgrow soil/ha maintained higher straw yield (53.53 q/ha) and test weight (42.20 g) due to application of 100 % NPK along with 300 kg wellgrow soil/ha whereas it was at par with application of 75% and 100% NPK with both levels of wellgrow formulation.